Factores de riesgo psicosociales asociados a la depresión en adultos mayores - Bermeo Ordóñez, Kerlyn Michelle (2023)
Aging is a natural and heterogeneous process that affects everyone in a unique way, it is influenced by various psychosocial factors, and can be a positive experience or be associated with disorders. Depression is one of the most common diseases in old age because of biological, psychological, and social factors. In view of this problem, the present study aimed to describe the scientific evidence of psychosocial risk factors associated with depression in older adults in Latin America. A qualitative, non-experimental, cross-sectional, and descriptive literature review was conducted. Scientific articles were searched in databases such as Redalyc, Dialnet, Google academic and Scielo published between the years 2013 to 2023, selecting 13 scientific articles as a representative sample of the research. The results of the study indicated that there are psychological risk factors such as: feeling hopelessness, living alone, having a negative perception of the quality of life, fear of death, feelings of loneliness, feelings of inactivity, difficulties in adapting to the situation of widowhood, suffering from organic diseases, maladaptation to retirement, compulsive behaviors, dependency, and low self-esteem. As for social risk factors, we found lack of social contact and support, social isolation, lack of employment, abandonment of tasks and hobbies due to health status, non-participation in family activities, alcohol consumption and little or no social interaction. In relation to sociodemographic characteristics, age (between 70 and 79 years), gender (female), marital status (single, divorce/separation or widowhood), educational level (none or low) and residence in (rural area), are those associated with the occurrence of depression in older adults. Finally, an intergenerational program model is proposed with the objective of promoting active aging and preventing depression in older adults